Work Readiness Shaped by Family, Information Systems, and Organizational Activeness: Kesiapan Kerja Dipengaruhi oleh Keluarga, Sistem Informasi, dan Aktivitas Organisasi - Rosa, Deshiamiar; Sumartik (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Higher education institutions in Indonesia are challenged to produce competent graduates who can compete in the global workforce. Specific background: At Muhammadiyah University of Sidoarjo, tracer study data show that the graduation rate remains below 50%, largely due to suboptimal work readiness among students. Knowledge gap: While previous studies address factors influencing employability, limited attention has been given to the simultaneous role of the family environment, information systems, and organizational activeness in shaping work readiness. Aims: This study investigates the contribution of these three factors to the work readiness of management students. Results: Using a quantitative approach with 317 active students and multiple linear regression analysis through SPSS, the findings demonstrate that the family environment, information systems, and organizational activeness collectively and significantly shape student work readiness. Novelty: The study integrates academic, social, and technological dimensions in one model, offering a holistic perspective on graduate preparedness. Implications: The results provide insights for universities to strengthen family engagement, optimize information systems, and encourage organizational participation as strategies to enhance student readiness for employment. Highlights: Graduation rate below 50% linked to weak work readiness. Three factors collectively determine student readiness for employment. Integrated approach provides strategic insights for higher education. Keywords: Family Environment; Information Systems; Organizational Activeness; Work Readiness; Higher Education